(untitled) (Journal of Student Affairs in Africa, 2024)
The transition into higher education is a challenging process for many students. Students are often underprepared academically (amongst other aspects). This under-preparedness influences students’ subsequent academic performance, and ultimately, overall student success. Research has shown that successful student transition into higher education can set the foundation for success at university. A transition programme (Step-Up) was offered to Bachelor of Commerce students before the start of the first semester to better prepare students academically and assist with the transition into higher education. The causal-comparative research design that was adopted demonstrated that in their first semester, the students who attended the transition programme consistently performed better academically than those who did not. Transition programmes can be a valuable form of early academic intervention that can and should be employed to cultivate student success and furthermore enable students to feel more prepared for higher education.